Educational Game Introduction to the North Sumatra State Museum Building using RPG Maker MV - Gufhron, Rodjil; Ari Usman, (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This study aims to develop an educational game titled "Introduction to the North Sumatra State Museum" to enhance young people's understanding of Indonesia's history, culture, and natural wealth. The game was developed using RPG Maker MV to create an accessible 2D educational game and applies the Finite State Machine (FSM) method to manage interactions with non-player characters (NPCs). A qualitative approach was used, with data collected through questionnaires distributed to 30 respondents aged 15–25. The evaluation focused on gameplay, functionality, and cross-platform compatibility. Results showed that 76% of respondents felt engaged during gameplay, while 74% agreed that the game was effective as an educational tool. Additionally, 74% of respondents stated that the game is suitable to be used as a learning medium for introducing the North Sumatra State Museum.